Accounting and the global economy after Sarbanes-Oxle - Garner, Don E.; McKee, David L.; McKee, Yosra AbuAmara 1948- (M.E. Sharpe, 2007)
This book is essential for students and practitioners in accounting, international business, finance, and economics. In a straightforward and readable style, it focuses on the changing accounting and auditing standards in national and global economies in the post-Enron/Arthur Andersen era